Las organizaciones comunitarias como instituciones intermedias: las Juntas de Acción Comunal en el municipio de Tenjo (2013)
This article is based on research: “The community organizations and intermediary institutions, applied to the Community Action Committees (JAC) in the municipality of Tenjo” that was conducted for degree as Sociologist. The focus of the article is to explain the change in the functionality of the JAC as intermediary institutions, in terms of its organizational structure and its relationship with the state and the community.